Corporatization and corporate social responsibility insurance, banking, industrial design, ownership and control - Das, Dipak (SBS Pub. & Dist., 2011)
This scholarly work is both broad in scope and extremely rich in detail. The readers will find this a useful reference book as well as a general text for scholar, researcher of Management Studies and law students specializing in Corporate Law for there under graduate and post graduate studies.